2023
DOI: 10.1111/bph.16190
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic nitazoxanide protects against experimental pulmonary fibrosis

Abstract: Background and PurposeNitazoxanide is a therapeutic anthelmintic drug. Our previous studies found that nitazoxanide and its metabolite tizoxanide activated adenosine 5′‐monophosphate‐activated protein kinase (AMPK) and inhibited signal transducer and activator of transcription 3 (STAT3) signals. As AMPK activation and/or STAT3 inhibition are targets for treating pulmonary fibrosis, we hypothesized that nitazoxanide would be effective in experimental pulmonary fibrosis.Experimental ApproachThe mitochondrial oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 63 publications
0
0
0
Order By: Relevance
“…Nitazoxanide is bio-transformed into active metabolite tizoxanide after absorption in mammals. Both nitazoxanide and tizoxanide have mitochondrial uncoupling effects 17 , 18 , 35 , 36 . Nitazoxanide has been a clinical antiprotozoal drug with good safety profile, in the present study, we found that nitazoxanide and its metabolite tizoxanide extended the healthspan of wild type C. elegans , improved the shortened C. elegans lifespan induced by high-glucose.…”
Section: Discussionmentioning
confidence: 99%
“…Nitazoxanide is bio-transformed into active metabolite tizoxanide after absorption in mammals. Both nitazoxanide and tizoxanide have mitochondrial uncoupling effects 17 , 18 , 35 , 36 . Nitazoxanide has been a clinical antiprotozoal drug with good safety profile, in the present study, we found that nitazoxanide and its metabolite tizoxanide extended the healthspan of wild type C. elegans , improved the shortened C. elegans lifespan induced by high-glucose.…”
Section: Discussionmentioning
confidence: 99%